Poverty and the WTO : Impacts of the Doha Development Agenda - Hertel, Thomas W.; Winters, L. Alan (Washington, DC: World Bank and Palgrave Macmillan, 2012)
This study reports on the findings from a major international research project investigating the poverty impacts of a potential Doha Development Agenda (DDA). It combines in a novel way the results from several strands of research. First, it draws on an intensive analysis of the DDA Framework Agreement, with particularly close attention paid to potential reforms in agriculture. The scenarios are built up using newly available tariff line data, and their implications for world markets are established using a global modeling framework. These world trade impacts form the basis for 12 country case studies of the national poverty impacts of these DDA scenarios. The focus countries are Bangladesh, Brazil (2 studies), Cameroon, China (2 studies), Indonesia, Mexico, Mozambique, the Philippines, the Russian Federation, and Zambia. Although the diversity of approaches taken in these studies limits the ability to draw broader conclusions, an additional study that provides a 15-country cross-section analysis is aimed at this objective. Finally, a global analysis provides estimates for the world as a whole.